Vertical integration and long-term contracts in risky markets - Fridrik M. Baldursson; Nils-Henrik M. von der Fehr (University of Oslo, Department of Economics, 2007)
We consider the effects of vertical integration on the performance of long-term and spot markets when spot prices are uncertain and agents are risk averse. We find that vertical integration impairs market performance by increasing the gap between contract and (expected) spot prices. This holds regardless of whether retail prices are fixed or linked to spot prices. Depending upon the characteristics of demand and supply, vertical integration (and long-term contracting) may increase or decrease spot-price volatility.
Keywords: A10; 330; Vertical integration; long-term contracts; spot markets; risk aversion; electricity markets; Energiemarkt; Vertikale Konzentration; Vertragstheorie; Spotmarkt; Dauer; Risikoaversion; Theorie